COMMUNICATION STRATEGIES OF THE SUKALAKSANA VILLAGE COMMUNITY IN MAINTAINING CULTURE AND DEVELOPING ECOTOURISM - widya pradhana, Mahendra Abifathir; Santosa, Aditya Putra Pratama (Jurnal Spektrum Komunikasi, 2025)
Sukalaksana Village is one of the villages in Garut Regency, West Java Province, which still preserves local cultural values and develops local wisdom-based ecotourism potential. As a tourist village with the Saung Ciburial Tourism Village branding, Sukalaksana Village uses special communication methods to preserve and maintain their culture and make it the center of attention in developing ecotourism. This study aims to understand how the communication strategies carried out by the people of Sukalaksana Village in preserving local cultural values while developing ecotourism potential rooted in local wisdom. Using a qualitative approach with ethnographic methods, data were collected through semi-structured interviews, observation, and documentation. The results showed that the Sukalaksana Village community implemented three strategies to preserve their culture and outlined three communication strategies used to develop ecotourism. In addition, cross-sectoral communication with the government, community, and tourists is key in the development of sustainable ecotourism. This communication strategy not only plays a role in preserving cultural identity but also strengthens community participation in ecotourism management. The conclusion of this research is that the success of Sukalaksana Village in preserving culture and developing ecotourism is strongly influenced by the communication strategy that is used to promote ecotourism. This strategy not only strengthens the community's cultural identity, but also creates economic opportunities through sustainable tourism.